Complement System in Dermatological Diseases – Fire Under the Skin - Panelius, Jaana; Meri, Seppo (Frontiers in Medicine, 2015)
The complement system plays a key role in several dermatological diseases. Overactivation, deficiency or abnormality of the control proteins are often related to a skin disease. Autoimmune mechanisms with autoantibodies and a cytotoxic effect of the complement membrane attack complex (MAC) on epidermal or vascular cells can cause direct tissue damage and inflammation e.g. in SLE, phospholipid antibody syndrome and bullous skin diseases like pemphigoid. By evading complement attack, some microbes like borrelia spirochetes and staphylococci can persist in the skin and cause prolonged symptoms. In this review we present the most important skin diseases connected to abnormalities in the function of the complement system. Drugs having an effect on the complement system are also briefly described. On one hand, drugs with free hydroxyl on amino groups (e.g. hydralazine, procainamide) could interact with C4A, C4B or C3 and cause an SLE-like disease. On the other hand, progress in studies on complement has led to novel anti-complement drugs (recombinant C1 inhibitor and anti-C5 antibody, eculizumab) that could alleviate symptoms in diseases associated with excessive complement activation.The main theme of the manuscript is to show how relevant the complement system is as an immune effector system in contributing to tissue injury and inflammation in a broad range of skin disorders.